A Systematic Review and Meta-Analysis on the Epidemiology of Hepatitis B and Hepatitis C Virus among Beta-Thalassemia Major Patients in Pakistan - Waheed, Usman; Saba, Noore; Wazeer, Akhlaaq; Ahmed, Saeed (Journal of Laboratory Physicians, 2021)
Beta-thalassemia major patients are the leading consumers of blood transfusions in Pakistan and, therefore, have a greater risk of acquiring transfusion-transmitted infections, most notably hepatitis B and C virus (HBV and HCV). The present study includes a comprehensive review on the status of HBV and HCV in beta-thalassemia major patients in Pakistan. For this purpose, we examined original articles assessing the epidemiology of HBV and HCV in transfusion-dependent thalassemia patients.We searched 10 major subscription databases from January through February 2020, that is, Medline, PakMediNet, CINAHL, Scopus, PubMed, Web of Science, Embase, Science Direct, Google Scholar, and Directory of Open Access Journals. The World Health Organization resources were also explored for relevant reports. The search criteria included published articles up to December 31, 2019, with no language restrictions. Articles identified were introduced into the Endnote version X9 software and then screened for relevance and duplication. The results were stated as the pooled prevalence for the overall study and also for region-wise subgroups.A total of 33 studies conducted from 1995 to 2019 were included in the review. All 33 articles yielded information on HCV prevalence, while 19 of them provided information on HBV prevalence. The overall sample size was 8,554 that tested the prevalence of HCV in thalassemia patients. The sample size from the 19 studies that tested the prevalence of HBV was 6,184. The overall pooled prevalence of HBV was computed to be 4.13%, while the pooled prevalence of HCV was 29.79%. The majority of the studies were obtained from the Punjab Province (33.33%), followed by Khyber Pakhtunkhwa Province (24.24%).The total sample size of 33 studies was less than 10% of the total number of estimated thalassemic patients, that is, 100,000. Further studies or a national baseline survey are imperative to confirm the actual frequency of HBV and HCV in thalassemia patients across the country.
Keywords: Keywords; thalassemia; hepatitis B; hepatitis C; epidemiology; Pakistan